Risk factors for Epstein–Barr virus reactivation after renal transplantation: Results of a large, multi‐centre study. (26th August 2021) - Blazquez‐Navarro, Arturo; Dang‐Heine, Chantip; Wehler, Patrizia; Roch, Toralf; Bauer, Chris; Neumann, Sindy; Blazquez‐Navarro, Rodrigo; Kurchenko, Andriy; Wolk, Kerstin; Sabat, Robert; Westhoff, Timm H.; Olek, Sven; et al.
Summary: Epstein–Barr virus (EBV) reactivation is a very common and potentially lethal complication of renal transplantation. However, its risk factors and effects on transplant outcome are not well known. Here, we have analysed a large, multi‐centre cohort ( N = 512) in which 18.4% of the patients experienced EBV reactivation during the first post‐transplant year. The patients were characterized pre‐transplant and two weeks post‐transplant by a multi‐level biomarker panel. EBV reactivation was episodic for most patients, only 12 patients showed prolonged viraemia for over four months. Pre‐transplant EBV shedding and male sex were associated with significantly increased incidence of post‐transplant EBV reactivation. Importantly, we also identified a significant association of post‐transplant EBV with acute rejection and with decreased haemoglobin levels. No further severe complications associated with EBV, either episodic or chronic, could be detected. Our data suggest that despite relatively frequent EBV reactivation, it had no association with serious complications during the first post‐transplantation year. EBV shedding prior to transplantation could be employed as biomarkers for personalized immunosuppressive therapy. In summary, our results support the employed immunosuppressive regimes as relatively safe with regard to EBV. However, long‐term studies are paramount to support these conclusions. Abstract : We have performed a thorough analysis of the risk factors and consequences of Epstein‐Barr virus reactivations after kidney transplantation. Detectable viral loads pre‐transplantation were a novel risk factor. Our data suggest that the employed immunosuppression is safe with regard to Epstein–Barr virus.